Sierra Leone : First Review Under the Extended Credit Facility Arrangement, Request for Modification of Performance Criteria, and Financing Assurances Review-Staff Report; and Press Release. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2014)
This paper discusses Sierra Leone's First Review Under the Extended Credit Facility (ECF) Arrangement, Request for Modification of Performance Criteria (PC), and Financing Assurances Review. Program performance has been strong. All PCs were met with comfortable margins, and all indicative targets (ITs) were met, except for the one on poverty-related spending that was missed owing to enhanced monitoring of domestic investment execution and delayed budget support. Economic growth momentum continued in 2013, with output expanding by 20 percent. The IMF staff recommends completion of the first review under the ECF arrangement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet